Metabolite data of germinated Bambara groundnut flour and starch extracted with two different solvents - Oyedeji, Ajibola Bamikole; Chinma, Chiemela Enyinnaya; Green, Ezekiel (Data in Brief, 2021)
The data presented in this study represents the profile ofmetabolites of germinated Bambara groundnut flour (GBF) and starch (GBS) extracted using two different extraction solvents. Bambara groundnuts obtained from a local agro market in Minna, Niger State, Nigeria were germinated at 28 ± 1°C for 24, 48 and 72 h, dried and then processed into flour and starch. Raw Bambara groundnuts (0 h) were also processed into flour and starch and served as controls. Samples at the different germination times were extracted using methanol/water (80:20v/v) and acetonitrile/methanol/water (40:40:20 v/v/v), concentrated, reconstituted and analysed on a gas chromatography-high resolution time of flight-mass spectrometer (GC-HRTOF-MS). Data obtained were classified into compound groups such as acids, alcohols, cyclic compounds, esters, ketones, phytosterols, vitamins and many others, and their characteristics such as the retention time, observed mass, molecular formular and mean peak areas were reported. These data represent the collection of metabolites in GBF and GBS and may be useful for the identification and utilization of functional compounds in foods
Keywords: Metabolites; GC-HRTOF-MS; Bambara groundnut; Germination; Solvent extraction; Oluwafemi Ayodeji Adebo; ACE: Mycotoxin and Food Safety; Federal University of Technology, Minna; ACEMFS; Nigeria